Effect of Lactobacillus plantarum on Total Immunoglobulin E Serum and Scoring Atopic Dermatitis (SCORAD) Index in Children With Atopic Dermatitis - Renata Prameswari; Linda Astari; Afif Nurul Hidayati; Cita Rosita Sigit Prakoeswa (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2017)
Background: The prevalence of atopic dermatitis (AD) has been increased for several decades. T-helper cell (Th)1 and Th2 disregulation influence the level of immunoglobulin (Ig)E and interfere Scoring Atopic Dermatitis (SCORAD) index. Management approachment only relieved the symptoms, therapy with probiotic are potentially  improve this disregulation. Lactobacillus plantarum (LP) has been fullfilled as probiotic criteria and it’s safely used in human. Methods: In a randomized, double-blind, placebo-controlled trial, twenty (22) patients were randomized to take LP or placebo for 12 weeks with 2 weeks wash-out period in Pediatric Division, Dermatology and Venereology Outpatient Clinic. Total IgE serum level  and SCORING indeks were evaluted before and after intervention. Results: Twelve (12) patients in probiotic group and 10 patient in placebo group completed the study. Our findings revealed that there is no significant different in total IgE serum between LP (504.533 IU/ml ± 415.686 IU/ml) and placebo (909.580 ± 885.051 IU/ml) respectively (p=0.117). Mean decreased difference of SCORAD index in LP group (36.784 ± 8.705) significant greater than placebo (26.860 ± 5.021) respectively (p= 0.000). Conclusion: Total IgE serum in both group not significantly different. However, SCORAD indeks in LP group showed a significantly greater reduction.  LP is beneficial in the treatment of children with AD.